Development of an Augmented Reality Learning Application to Introduce Animal Concepts for Early Childhood Education - Zainul Arifin; Alfarobi Ahmad Sulaiman; Azkiya Jihadi A'la; Mutiara Fahrunisa; Siti Hajar (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This research aims to describe the process of developing Augmented Reality (AR) applications as an interactive and effective learning medium for animal world materials. The research method used is a research and development (R&D) model with a qualitative and quantitative approach. The development process includes analyzing user needs, designing and implementing the application, and evaluating the effectiveness of its use in the classroom. The results of the study show that AR applications are able to provide a more real and interesting learning experience for students. Key features such as 3D displays of animals, sounds, and interactive information successfully improve student engagement and understanding of the material. Analysis of students' responses showed that the majority felt more motivated and easily understood concepts about the animal world through this medium. The implications of this study show that AR technology has great potential in increasing learning effectiveness, especially in materials that require high visualization. Further development and integration with the curriculum can expand its benefits in the world of education.